Optimization of CRISPR/Cas System for Improving Genome Editing Efficiency in Plasmodium falciparum - Zhao, Yuemeng; Wang, Fei; Wang, Changhong; Zhang, Xiaobai; Jiang, Cizhong; Ding, Feng; Shen, Li; Zhang, Qingfeng (Frontiers in Microbiology, 2021)
For a long time, the studying of molecular mechanisms leading to malaria and related gene functions has been greatly restricted by limited genome editing technologies. Recently a simple and effective genome editing technology, CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated) system, has greatly facilitated these studies in many organisms including malaria parasites. However, due to the special parasitic status, the efficacy of CRISPR/Cas system in malaria parasites is greatly reduced. Herein, based on the CRISPR/Cas9 system, we developed an integrating strategy to generate a Cas9i system, which can greatly increase the speed of obtaining transgenic strains of Plasmodium falciparum. Moreover, with this Cas9i system, we have successfully achieved multiplex genome editing (mutating or tagging) in P. falciparum. In addition, we firstly adapted AsCpf1, an alternative to Cas9, to P. falciparum parasites for efficient genome editing. These optimizations of the CRISPR/Cas system may further facilitate the research of malaria parasites and help to eliminate malaria in the future.